The improvement of future teachers' professional training based on a culturalogical approach - Halyna Boryn (Vasyl Stefanyk Precarpathian National University, 2017)
It is analyzed the scientists' views on the problem of formation of a future teacher'sprofessional culture in the universities conditions and it is outlined the best ways for culturaldevelopment of student's personality in the educational process of higher educationalinstitution in the article. Key word: professional training, professional culture, cultural development,professional and personal qualities.